Optimalisasi Prinsip Kepentingan Terbaik Anak dalam Penetapan Hak Asuh Pasca Perceraian : Perspektif Hukum Islam dan Hukum Positif di Indonesia - Ananda Sabina Zahira (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Divorce has a significant impact on a child's psychological and social development, particularly in the aspect of determining custody rights, which should prioritize the principle of the child's best interests. This study aims to analyze the balance between Islamic legal norms as stipulated in the Compilation of Islamic Law (KHI) and positive law in Indonesia, in cases where children under the age of 12 express a desire to live with their father after the divorce. The research approach used is a juridical-normative with a qualitative analysis method that focuses on a literature review of laws and regulations such as the KHI, the Marriage Law, the Child Protection Law, and the Convention on the Rights of the Child, as well as relevant legal and jurisprudential literature. The results of the study indicate that although normatively the KHI prioritizes the mother as the caregiver of children under 12 years old, there is room for flexibility that allows the court to consider the child's wishes if it better ensures the child's welfare and safety. This approach is supported by the principle of maslahah mursalah in Islamic law, which allows adjustments for the benefit of the child. The main challenges in its implementation include the minimal involvement of professionals such as child psychologists in the evaluation process, the existence of gender stereotypes that influence judges' decisions, and emotional conflicts between parents that often override the interests of the child. Therefore, this study recommends that judicial institutions actively involve psychologists and mediators in custody proceedings, improve training for judges in understanding the psychosocial dynamics of children, and update legal guidelines so that children's wishes can be assessed objectively. Furthermore, education to the wider public about the importance of gender non-discrimination in child care is also needed so that custody decisions truly reflect the principles of comprehensive child protection and welfare.